Estrategias metodológicas en niños con disgrafía del cuarto de educación básica de la Unidad Educativa Esparza Moreno del cantón Babahoyo Provincia de Los Ríos 2023 - Mejia Andino, Evelin Maylin (2023)
In the present research project, the methodological strategies in children with dysgraphia in the basic education room of the Esparza Moreno Educational Unit of the Babahoyo canton, Provincia de los Ríos, the degree of dysgraphia present in the institution along with the mythological strategies used, also on the Implementation of the methodological strategies that should be used and types of specific strategies or guides for children who have this type of disorder or learning problems in school, mentioning that depending on the complexity. This being a reference for the use of methodological strategies, considered adaptive for each case. Along with the identification of the existing types of dysgraphia that are affected in the academic performance of children from the motor part being the most affected and visible or in relation to the dyslexic part. Demonstrating through the evaluation tests the result of the degree of dysgraphia of the fourth grade children of basic education of the Esparza Moreno Educational Unit of the Babahoyo canton, Province of los Ríos. Culminating with the intervention of a practical guide aimed at tutor teachers in charge of students who have this disorder in the language area focused on the writing part.